CTC-Based Learning of Chroma Features for Score-Audio Music Retrieval - Zalkow, Frank; Müller, Meinard (IEEE/ACM Transactions on Audio, Speech and Language Processing, 2021)
This paper deals with a score-Audio music retrieval task where the aim is to find relevant audio recordings of Western classical music, given a short monophonic musical theme in symbolic notation as a query. Strategies for comparing score and audio data are often based on a common mid-level representation, such as chroma features, which capture melodic and harmonic properties. Recent studies demonstrated the effectiveness of neural networks that learn task-specific mid-level representations. Usually, such supervised learning approaches require score-Audio pairs where the score's individual note events are aligned to the corresponding time positions of the audio excerpt. However, in practice, it is tedious to generate such strongly aligned training pairs. As one contribution, we show how to apply the Connectionist Temporal Classification (CTC) loss in the training procedure, which only uses weakly aligned training pairs. In such a pair, only the time positions of the beginning and end of a theme occurrence are annotated in an audio recording, rather than requiring local alignment annotations. We evaluate the resulting features in our theme retrieval scenario and show that they improve the state of the art for this task. As a main result, we demonstrate that with the CTC-based training procedure using weakly annotated data, we can achieve results almost as good as with strongly annotated data. Furthermore, we assess our chroma features in depth by inspecting their temporal smoothness or granularity as an important property and by analyzing the impact of different degrees of musical complexity on the features.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Alignment; audio; chroma features; CTC loss; deep learning; music retrieval; musical themes